Speech at the World Food Security Summit, in Rome, June 6, 2008 - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, discussed three critical needs: (i) meeting the immediate requirements of 20 of the most vulnerable countries; (ii) getting seeds, fertilizers, and inputs to those developing countries where smallholder farmers can expand production this season; and (iii) an removing export bans and restrictions.